Customers satisfaction towards SESB front office desk and bill payment counter / Vanessa Serena Stephen - Stephen, Vanessa Serena (2011)
This research is being done to identify the level of customers satisfaction toward SESB ( Sabah Electricity Sdn Bhd) Front office and bill payment services. The scope of the research will be covered the customers from Kota Kinabalu area which dealing with SESB front office and bill payment counter. Questionnaire method wil be used in this research, whereby the customers who dealing with SESB front ofice and payment counter will be given the questionnaire to answer 24 questions about front office desk and bill payment counter. From the findings, most of the respondents did not satisfify with the waiting time for the services to be given and the facilities provided by the company. This is the major problem faced by the customers. In conclusion, SESB management should take action to overcome this problem. It is because, SESB is monopoly business where they should appreciate their customers.